2007
DOI: 10.1038/nature06336
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila proteins that regulate Rab1 membrane cycling

Abstract: Rab1 is a GTPase that regulates the transport of endoplasmic-reticulum-derived vesicles in eukaryotic cells. The intracellular pathogen Legionella pneumophila subverts Rab1 function to create a vacuole that supports bacterial replication by a mechanism that is not well understood. Here we describe L. pneumophila proteins that control Rab1 activity directly. We show that a region in the DrrA (defect in Rab1 recruitment A) protein required for recruitment of Rab1 to membranes functions as a guanine nucleotide di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
356
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(363 citation statements)
references
References 34 publications
5
356
0
2
Order By: Relevance
“…We found no significant difference in the k cat /K m of DrrA 340-533 toward WT Rab1 and Rab1T75E, and only a slight difference with Rab1T75A; thus, we infer that it is unlikely phosphorylation of T75 prevents Rab1 interaction with GEFs or interferes with activation. Phosphomimetic mutant Rab1T75E yields similarly insignificant effects on the ability of a Legionella GAP, LepB (33), to stimulate Rab1 hydrolysis of GTP, as measured with the Promega GTPase-Glo system (34). Briefly, increasing concentrations of LepB with excess GTP held at a constant concentration are added to wells containing a constant concentration of Rab1 and allowed to react for 1 h. The amount of remaining, unhydrolyzed GTP in each condition is detected by luminescencecoupled assay, plotted against GAP concentration, and a LepB EC 50 is determined.…”
Section: Resultsmentioning
confidence: 99%
“…We found no significant difference in the k cat /K m of DrrA 340-533 toward WT Rab1 and Rab1T75E, and only a slight difference with Rab1T75A; thus, we infer that it is unlikely phosphorylation of T75 prevents Rab1 interaction with GEFs or interferes with activation. Phosphomimetic mutant Rab1T75E yields similarly insignificant effects on the ability of a Legionella GAP, LepB (33), to stimulate Rab1 hydrolysis of GTP, as measured with the Promega GTPase-Glo system (34). Briefly, increasing concentrations of LepB with excess GTP held at a constant concentration are added to wells containing a constant concentration of Rab1 and allowed to react for 1 h. The amount of remaining, unhydrolyzed GTP in each condition is detected by luminescencecoupled assay, plotted against GAP concentration, and a LepB EC 50 is determined.…”
Section: Resultsmentioning
confidence: 99%
“…One of these, LepB, is a GAP for Rab1 that localizes to LCVs (Ingmundson et al, 2007). In terms of amino acid sequence, it is not related to eukaryotic GAPs, suggesting there might be structural and mechanistic differences compared to the TBC domain GAPs characterized so far.…”
Section: Learning About Vesicular Transport From Bacteriamentioning
confidence: 99%
“…It was therefore of great interest when it was reported that DrrA (or SidM), one of the ca. 300 so-called effector molecules injected into the cytoplasm of cells infected by L. pneumophila, has the properties of a GDF as well as those of a GEF towards Rab1 and is important for the localization of host-cell Rab to the Legionella containing vacuoles (LCVs) (Ingmundson et al, 2007;Machner and Isberg, 2007), which are compartments generated in infected cells by the bacteria for their own replication. Subsequently, it was shown that while DrrA does indeed have GEF properties towards Rab1, it does not have discrete GDF properties, i.e.…”
Section: Learning About Vesicular Transport From Bacteriamentioning
confidence: 99%
“…A study by Hoffmann et al characterized the bacterial LCV proteome at 1h after infection (29). Hoffmann et al found some of the here described PE-up proteins, including RavZ (124), RalF (119), SidC (111,162), SidM/DrrA (113,115,163) but also some E-up proteins, such as LegS2 (105), LepA (108), and those with equal abundance, such as Lem3 (164), Ceg28/ RidL (165), SdhA (166), SidD (110,167). This shows that a broad variety of Dot/Icm effectors is present in LCV proteomes.…”
Section: Overview Of L Pneumophila E and Pe Soluble Whole Cellmentioning
confidence: 99%